Implementation of Village Fund Policy in The Development of Tourist Villages to Encourage Village Independence - Sugito; MT, Ika Sartika (Manunggal Halim Jaya, 2025)
The implementation of the Village Fund policy since 2015 has significantly contributed to rural economic development and increased village independence in Indonesia. With a total allocation of Rp 539 trillion distributed to approximately 74,960 villages by 2023, the Village Fund enables villages to finance development based on local potential, particularly in the tourism sector. Data shows an increase in fund allocation per village from approximately Rp 280 million in 2015 to Rp 1.1–1.3 billion in 2023, with an average absorption rate of 99%. This program has proven effective in reducing the poverty rate in villages from 14.21% in 2015 to 12.22% in 2023, which is higher than the decline in urban areas. In addition, the number of independent villages has increased significantly, from 174 villages in 2015 to 11,456 villages in 2023, while the number of underdeveloped villages has decreased drastically from 33,592 to 7,154 villages. This increase reflects the effectiveness of the Village Fund in promoting independence through local economic development, particularly through the arts, culture, and nature-based tourism sector. However, challenges remain, including transparent management and the development of original village revenue sources to ensure future economic sustainability. Therefore, the Village Fund serves not only as a fiscal instrument but also as a catalyst for strengthening inclusive and sustainable village development.